IMPLEMENTATION OF TAX INCENTIVES ON SALES ON LUXURY GOODS BORNE BY THE GOVERNMENT FOR AUTOMOTIVE INDUSTRY AFTER COVID-19 PANDEMIC - Ramadhena, Citra Yadin; Tambunan, Maria R.U.D. (Dialogue : Jurnal Ilmu Administrasi Publik, 2024)
The Covid-19 pandemic has downturned the business sector in Indonesia. This prompted the government to provide tax incentives through the National Economic Recovery program. To encourage people's purchasing power, support businesses, and restore economic conditions, the government issued a Sales Tax on Luxury Goods borne by the government (PPnBM Ditanggung Pemerintah/PPnBM DTP) incentive for the automotive industry. This study aims to analyze the PPnBM DTP after the Covid-19 and analyze the government's considerations to extend the policy. This research applied post-positivist approach with qualitative research method. The data was collected through literature review and interview. The research shows that implementing this policy produces several benefits. However, it also has an anomaly. The community, especially the lower middle class, faces difficult conditions, but on the other hand, the middle class is encouraged to spend their money. The implementation of this policy also does not experience significant obstacles because adequate resources and communication for implementing policy is established smoothly. The policy has succeeded in maintaining enthusiasm, people's purchasing power and lead to a positive response from various parties. In addition, extension of the policy, 100% PPnBM DTP has been made by considering both from a social and economic perspective.